2021
DOI: 10.1080/26939169.2021.1900759
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Algorithmic Models to Develop Secondary Teachers’ Understanding of the Statistical Modeling Process

Abstract: Statistical modeling continues to gain prominence in the secondary curriculum, and recent recommendations to emphasize data science and computational thinking may soon position algorithmic models into the school curriculum. Many teachers' preparation for and experiences teaching statistical modeling have focused on probabilistic models. Subsequently, much of the research literature related to teachers' understanding has focused on probabilistic models. This study explores the extent to which secondary statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…As Sulmont et al [20] found for non‐majors at the university level, it is more difficult to teach reasoning about machine learning models than it is to teach the algorithms, yet it is possible [19]. Regarding teacher education, Zieffler et al [22] recently noted that, analogously for mathematics teachers, decision tree algorithms can be taught well in in‐service training, but the evaluation of decision trees is a greater challenge. In our module, we focus on both decision tree algorithms and their evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…As Sulmont et al [20] found for non‐majors at the university level, it is more difficult to teach reasoning about machine learning models than it is to teach the algorithms, yet it is possible [19]. Regarding teacher education, Zieffler et al [22] recently noted that, analogously for mathematics teachers, decision tree algorithms can be taught well in in‐service training, but the evaluation of decision trees is a greater challenge. In our module, we focus on both decision tree algorithms and their evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Using machine learning for predictive modeling requires two things: the technical ability to create a predictive model and the ability to reason about the process to decide whether the resulting model is useful or just wrong, to refer again to the aphorism from the beginning of this paper. Different studies similarly report that difficulties often occur with reasoning about machine learning processes (Sulmont et al, 2019b;Zieffler et al, 2021) and with documentation in computational notebooks (Rule et al, 2018). Our findings suggest that our approach consisting of three aspects (teaching module, study a worked example, use the worked example as a scaffold) to address these difficulties seems to be promising to support students in applying, documenting, and reasoning about a machine learning process; here exemplified by the machine learning method of decision trees.…”
Section: Discussionmentioning
confidence: 54%
“…We intend to study how our teaching module (including our ProDaBi Decision Tree JNBs) and our worked example support students. Since Sulmont et al (2019a) and Zieffler et al (2021) found that it is challenging for students to reason about machine learning models, we are interested in how a worked example supports upper secondary students in creating, evaluating, and reasoning about a decision tree model after attending our teaching module. We wonder if they can use an interactive worked example to transfer a machine learning modeling process to a new problem and reason about it adequately.…”
Section: Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education researchers are re-thinking and expanding their ideas about data and approaches to statistical modelling and have suggested the inclusion of machine learning approaches and associated algorithmic models in high school curricula (e.g., Biehler & Schulte, 2017). From a learning perspective, algorithmic models could offer a more accessible and conceptually simpler mechanism to introduce students to data science than inferential methods (Gould, 2017;Ridgway, 2016), and research by Zieffler et al (2021) suggested there might be similar benefits for high school statistics teachers. Predictive modelling, with its focus on developing models by learning from features of data to make predictions and forecasts for likely future outcomes, could also provide opportunities for students to integrate both computational and statistical thinking (e.g., De Veaux et al, 2017).…”
Section: Teaching Predictive Modelling and Apismentioning
confidence: 99%